Derivatives of 9-phosphorylated acridine as butyrylcholinesterase inhibitors with antioxidant activity and the ability to inhibit β-amyloid self-aggregation: potential therapeutic agents for Alzheimer’s disease - Makhaeva, Galina F.; Kovaleva, Nadezhda V.; Rudakova, Elena V.; Boltneva, Natalia P.; Lushchekina, Sofya V.; Astakhova, Tatiana Yu; Timokhina, Elena N.; Serebryakova, Olga G.; Shchepochkin, Alexander V.; Averkov, Maxim A.; Utepova, Irina A.; Demina, Nadezhda S.; et al. (Frontiers in Pharmacology, 2023)
We investigated the inhibitory activities of novel 9-phosphoryl-9,10-dihydroacridines and 9phosphorylacridines against acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and carboxylesterase (CES). We also studied the abilities of the new compounds to interfere with the selfaggregation of β-amyloid (Aβ42) in the thioflavin test as well as their antioxidant activities in the ABTS and FRAP assays. We used molecular docking, molecular dynamics simulations, and quantum-chemical calculations to explain experimental results. All new compounds weakly inhibited AChE and off-target CES. Dihydroacridines with aryl substituents in the phosphoryl moiety inhibited BChE; the most active were the dibenzyloxy derivative 1d and its diphenethyl bioisostere 1e (IC50= 2.90±0.23 µM and 3.22±0.25 µM, respectively). Only one acridine, 2d, an analog of dihydroacridine, 1d, was an effective BChE inhibitor (IC50=6.90±0.55 µM), consistent with docking results. Dihydroacridines inhibited Aβ42 self-aggregation; 1d and 1е were the most active (58.9±4.7% and 46.9±4.2%, respectively). All dihydroacridines 1 demonstrated high ABTS •+ -scavenging and ironreducing activities comparable to Trolox, but acridines 2 were almost inactive. Observed features were well explained by quantum-chemical calculations. ADMET parameters calculated for all compounds predicted favorable intestinal absorption, good blood-brain barrier permeability, and low cardiac toxicity. Overall, the best results were obtained by two dihydroacridine derivatives 1d and 1e with dibenzyloxy and diphenethyl substituents in the phosphoryl moiety. These compounds displayed high inhibition of BChE activity and Aβ42 self-aggregation, high antioxidant activity, and favorable predicted ADMET profiles. Therefore, we consider 1d and 1e lead compounds for further in-depth studies as potential anti-AD preparations.